2018
DOI: 10.7567/jjap.57.07lc04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dissolved oxygen level of water on ultrasonic power measured using calorimetry

Abstract: Ultrasonic therapeutic equipment, which exposes the human body to high-power ultrasound, is used in clinical practice to treat cancer. However, the safety of high-power ultrasound has been questioned because the equipment affects not only cancer cells but also normal cells. To evaluate the safety of ultrasound, it is necessary to accurately measure the ultrasonic power of the equipment. This is because ultrasonic power is a key quantity related to the thermal hazard of ultrasound. However, precise techniques f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…As a result, bubbles trap in the antinodes of the sound pressure of the standing wave by the primary Bjerknes force are repelled [40] , and the number of bubbles decreases. When two bubbles expand and contract in the same phase, they are attracted by the secondary Bjerknes force, which is a kind of radiation force [39] , [40] . As the sound pressure and secondary Bjerknes force increase, the bubbles aggregate or coalesce, and they become larger and no longer contribute to the chemical reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, bubbles trap in the antinodes of the sound pressure of the standing wave by the primary Bjerknes force are repelled [40] , and the number of bubbles decreases. When two bubbles expand and contract in the same phase, they are attracted by the secondary Bjerknes force, which is a kind of radiation force [39] , [40] . As the sound pressure and secondary Bjerknes force increase, the bubbles aggregate or coalesce, and they become larger and no longer contribute to the chemical reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonic power P U was calculated as follows: where Δ T/ Δ t is the rate of the temperature rise, C p is the specific heat capacity of water, and M is the mass of water. The rate of the temperature rise was determined from the change in temperature in the initial stage of ultrasonic irradiation or before and after ultrasonic irradiation [39] . The sample volumes were 25, 50, 100, 150, and 200 mL.…”
Section: Methodsmentioning
confidence: 99%
“…We have developed techniques for the precise measurement of ultrasonic fields to evaluate the performance and safety of ultrasonic medical equipment and have provided related measurement standards. [1][2][3][4][5][6][7] In ultrasonic diagnosis, precise and practical measurement techniques are required for balancing patient safety during diagnosis 8,9) with improvement in diagnostic image brightness. 10) Therefore, a method based on the amplitude and phase frequency responses of hydrophone sensitivity, hereafter referred to as the deconvolution method, has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…16) Generally, acoustic pressure and ultrasonic power are used as an evaluation index for acoustic cavitation. 17,18) However, we previously reported that acoustic pressure cannot be used as an index for the generation position of acoustic cavitation. 19) In this study, we compared acoustic pressure and broadband noise, that is, the acoustic cavitation signals generated by bubbles.…”
Section: Introductionmentioning
confidence: 99%